Antibacterial activity and synergism of the essential oil of Nectandra megapotamica (L.) flowers against OXA-23-producing Acinetobacter baumannii. Issue 3 (3rd May 2020) - Vasconcelos, Nathalie Gaebler; Mallmann, Viviane; Costa, Érica Rodrigues; Simionatto, Euclésio; Coutinho, Eduardo João; De Lara Da Silva, Rogério César; Ribeiro, Suzana Meira; Franco, Octávio Luiz; Migliolo, Ludovico; Croda, Júlio; Simionatto, Simone
ABSTRACT: Multidrug-resistant Acinetobacter baumannii has emerged as a problematic hospital-acquired pathogen. It is vital to search for new sources of antibiotics. Natural plant essential oils have several biological properties, including antimicrobial activity and may be valuable for new drug development. Chemical composition of the essential oil of Nectandra megapotamica flowers was assessed by Gas Chromatography/Flame Ionization Detector and Gas Chromatography/Mass Spectrometry analysis. Antibacterial activity against OXA-23-producing A. baumannii and synergism with antibiotics were performed by broth microdilution, time kill, and checkerboard methods. The essential oil of Nectandra megapotamica flowers showed a predominance of oxygenated sesquiterpenes and caryophyllene oxide was the main component. Survival curves showed a linear decrease in viable OXA-23-producing A. baumannii cell counts over time for the association between the essential oil of Nectandra megapotamica flowers and imipenem. Checkerboard assay with imipenem presented Fractional Inhibitory Concentration Index of 0.156, suggesting synergism. The synergistic effect of essential oil of Nectandra megapotamica flowers with imipenem could be a potential approach to combat multiresistant OXA-23-producing A. baumannii strains, and could be used as a drug delivery system, as an excipient for imipenem, reducing its dosage.